2017
DOI: 10.1038/srep45833
|View full text |Cite
|
Sign up to set email alerts
|

The fate of patients with intermittent claudication in the 21st century revisited – results from the CAVASIC Study

Abstract: Patients with intermittent claudication carry a high risk for cardiovascular complications. The TransAtlantic Inter-Society Consensus (TASC) Group estimated a five-year overall mortality of 30% for these patients, the majority dying from cardiovascular causes. We investigated whether this evaluation is still applicable in nowadays patients. We therefore prospectively followed 255 male patients with intermittent claudication from the CAVASIC Study during 7 years for overall mortality, vascular morbidity and mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 29 publications
1
21
0
3
Order By: Relevance
“…41,42 In comparison, contemporary natural history studies of claudication demonstrate a more favorable outlook, with 5-year survival rates that range between 73% and 91%. [43][44][45][46] Consideration of those relative survival rates helps to contextualize the results from the meta-analysis by Katsanos et al, 7 which found the most pronounced mortality risk at the longer follow-up of 5 years, when most patients with ESRD would have succumbed to the disease or its complications. It is important that we interpret the paclitaxel safety signal alongside a complete understanding of the evidence for patient benefit that may be gained through the use of paclitaxel-coated balloon angioplasty in DA.…”
Section: Discussionmentioning
confidence: 99%
“…41,42 In comparison, contemporary natural history studies of claudication demonstrate a more favorable outlook, with 5-year survival rates that range between 73% and 91%. [43][44][45][46] Consideration of those relative survival rates helps to contextualize the results from the meta-analysis by Katsanos et al, 7 which found the most pronounced mortality risk at the longer follow-up of 5 years, when most patients with ESRD would have succumbed to the disease or its complications. It is important that we interpret the paclitaxel safety signal alongside a complete understanding of the evidence for patient benefit that may be gained through the use of paclitaxel-coated balloon angioplasty in DA.…”
Section: Discussionmentioning
confidence: 99%
“…McDermott et al [30] reported a 3-year cancer mortality rate of 3.0% in a cohort of 1314 PAD patients, corresponding to a 1-year annualized rate of 1.0% (i.e., approximately 5% through 5 years). Rantner et al [31] reported that cancer was the leading cause of death in a population of 255 intermittent claudication patients, occurring in 3.9% of patients (10/255) within 5 years. These published rates for cancer-related mortality in PAD patients are comparable to the rates seen in the Zilver PTX RCT (4.8%) and Japan PMS (3.0%) studies through 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with PAD have disease that affects multiple vascular beds, not only those vessels located in the lower extremities; they are therefore known to be at a high risk of MACE, even prior to undergoing an open or endovascular intervention. 22-24 The general anesthesia required for most LEB procedures coupled with potential blood loss drives the increased theoretical risk compared to IEI. For this reason, preference for IEI over LEB increases as surgical risk increases, as demonstrated in the baseline demographics of this study.…”
Section: Discussionmentioning
confidence: 99%